• Matéria: Matemática
  • Autor: lucaskaueneckel20
  • Perguntado 6 anos atrás

resolva as questoes a seguir

Anexos:

Respostas

respondido por: leticiagald920
1

Explicação passo-a-passo:

Regra de sinal:

( + ) × ( + ) = ( + )

( - ) × ( - ) = ( + )

( + ) × ( - ) = ( - )

( - ) × ( + ) = ( - )

a) (+11) × (+3) = 33

b) (-1) × (-5) = 5

c) (+9) × (-7) = -63

d) (-7) × (-7) = 49

e) 0 × (-10) = 0

f) (-11) × (+7) = -77

g) (-12) × (+23) = -276

h) (-16) × (-6) = 96

i) (-12) × (+12) =-144

j) (-20) × (+15) = -300

Perguntas similares